Early Upper Paleolithic human foot bones from Manot Cave, Israel. Issue 160 (November 2021) - Borgel, Sarah; Latimer, Bruce; McDermott, Yvonne; Sarig, Rachel; Pokhojaev, Ariel; Abulafia, Talia; Goder-Goldberger, Mae; Barzilai, Omry; May, Hila
Abstract: The transition from the Middle Paleolithic to the Upper Paleolithic in the Levant represents a major event in human prehistory with regards to the dispersal of modern human populations. Unfortunately, the scarcity of human remains from this period has hampered our ability to study the anatomy of Upper Paleolithic populations. This study describes and examines pedal bones recovered from the Early Upper Paleolithic period at Manot Cave, Israel, from 2014 to 2017. The Manot Cave foot bones include a partial, left foot skeleton comprising a talus, a calcaneus, a cuboid, a first metatarsal, a second metatarsal, a fifth metatarsal, and a hallucal sesamoid. All these remains were found in the same archaeological unit of the cave and belong to a young adult. Shape and size comparisons with Neanderthals, Anatomically Modern Human and modern human foot bones indicate a modern human morphology. In some characteristics, however, the Manot Cave foot bones display a Neanderthal-like pattern. Notably, the Manot Cave foot is remarkable in its overall gracility. A healed traumatic injury in the second metatarsal (Lisfranc's fracture) is most likely due to a remote impact to the dorsum of the foot. This injury, its subsequent debility, and the individual's apparent recovery suggest that the members of the Manot Cave community had a supportive environment, one with mutual responsibilities among the members.